European Integration and Income Convergence : Lessons for Central and Eastern European Countries - Martin, Carmela; Velazquez, Francisco J.; Funck, Bernard (Washington, DC: World Bank, 2013)
The prospect of enlarging the European Union (EU) to Central and Eastern European countries with income levels far below those of present members, questions how, and when the candidates' aspiration to converge towards EU standards of living, could possibly by fulfilled. To address these questions, this paper seeks to assess of the convergence experience of the four less developed EU members, i.e., Spain, Portugal, Ireland, and Greece, after joining the EU, and, to explore what lessons can be learned from that experience. The discussion suggests that, while theoretically possible, there is little empirical reason to fear that European integration would cause economies to diverge. Rather than being spontaneous, however, real convergence would seem to depend crucially, on the capacity of countries to tap international technological spillovers, particularly through foreign direct investment. Macroeconomic stability, effective competition on goods, and factor markets, and, a good human capital endowment are essential to harness benefits. Nonetheless, lingering worries about the possibility that integration would lead to real divergence between countries, or regions of Europe, has led to the creation of large transfers under the EU's Regional Policy. Pending more conclusive evidence of their effectiveness, the candidate countries would seem wise to put greater store by those domestic policies, than by EU grants to fuel their convergence.